2008
DOI: 10.1002/app.25160
|View full text |Cite
|
Sign up to set email alerts
|

Sheet molding compound characterization using spiral flow

Abstract: Sheet molding compound (SMC) is a fiberreinforced polymeric composite. It is often used in automotive, marine, and industrial applications over other materials because of its high strength to density ratio, resistance to corrosion, and low cost. There is a demand in the SMC industry to be able to characterize SMC processability. This is particularly true for heavy truck body panels, one of the fastest growing applications of SMC. Because of their large size and high strength requirement, the molding forces hav… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 20 publications
0
7
0
Order By: Relevance
“…It have also been observed that a higher ram velocity increases the flow of inner layers into deep ribs. 15 The complexity of the flow is further increased by curing, which, for example, have been shown by Rabinovich et al, 16 where a spiral flow tool, allowing long flows, were used to characterise SMC. The test showed that higher mould temperatures decreased the flow length for SMC.…”
Section: Introductionmentioning
confidence: 99%
“…It have also been observed that a higher ram velocity increases the flow of inner layers into deep ribs. 15 The complexity of the flow is further increased by curing, which, for example, have been shown by Rabinovich et al, 16 where a spiral flow tool, allowing long flows, were used to characterise SMC. The test showed that higher mould temperatures decreased the flow length for SMC.…”
Section: Introductionmentioning
confidence: 99%
“…It must be pointed out that such testing conditions, despite their simplicity, are not so far from the industrially encountered ones. Indeed, during the short duration of the compression mouldings, it is fair to assume [5] that the temperature of the compounds (i) is sufficiently low to avoid curing of the polymer and (ii) is approximately constant except near the lower and upper parts of the mould, where the heated polymer matrix acts as a lubricant [6,11,31,40,44].…”
Section: Comparison Experiments / Simulation Resultsmentioning
confidence: 99%
“…Rabinovich and co-authors have studied the rheological behavior of SMC using a spiral flow tool. 12 They evaluated the SMC flow, at high temperature, under pressure, for two CaCO 3 contents (56% and 65%). Their results show that the filler level within the ranges studied has little influence on the molding forces, contrary to glass level which has a greater effect.…”
Section: Resultsmentioning
confidence: 99%